Preterm Birth, Intrauterine Infection, and Fetal Inflammation - Kemp, Matthew W. (Frontiers in Immunology, 2014)
Preterm birth (delivery before 37 weeks’ gestation) is a leading cause of neonatal death and disease in industrialised and developing countries alike. Infection (most notably in high-risk deliveries occurring before 28 weeks’ gestation) is hypothesised to initiate an intrauterine inflammatory response that plays a key role in the premature initiation of labour as well as a host of the pathologies associated with prematurity. As such, a better understanding of intrauterine inflammation in pregnancy is critical to our understanding of preterm labour and fetal injury, as well as on-going efforts to prevent preterm birth. Focusing on the fetal innate immune system responses to intrauterine infection, the present paper will review clinical and experimental studies to discuss the capacity for a fetal contribution to the intrauterine inflammation associated with preterm birth. Evidence from experimental studies to suggest that the fetus has the capacity to elicit a pro-inflammatory response to intrauterine infection is highlighted, with reference to the contribution of the lung, skin and gastro-intestinal tract. The paper will conclude that pathological intrauterine inflammation is a complex process that is modified by multiple factors including time, type of agonist, host genetics, and tissue.